Large Amino Acid Mimicking Selenium-Doped Carbon Quantum Dots for Multi-Target Therapy of Alzheimer’s Disease - Zhou, Xi; Hu, Shuyang; Wang, Shuangling; Pang, Yu; Lin, Yulong; Li, Meng (Frontiers in Pharmacology, 2021)
Multi-target intervention and synergistic treatment are critical for the drug development of Alzheimer’s disease (AD) due to its complex and multifactional nature. Oxidative stress and amyloid β peptides (Aβ) accumulation have been recognized as therapeutic targets for AD. Herein, with ability to inhibit Aβ aggregation and the broad-spectrum antioxidant properties, the large amino acid mimicking selenium-doped carbon quantum dots (SeCQDs) are presented as novel nanoagents for multi-target therapy of AD. Compared with the precursor, selenocystine, SeCQDs which maintain the intrinsic properties of both selenium and carbon quantum dots (CQDs) possess good biocompatibility and a remarkable ROS-scavenging activity. Moreover, the functionalized α-carboxyl and amino groups on edge of SeCQDs can trigger multivalent interactions with Aβ, leading to the ability of SeCQDs to inhibit Aβ aggregation. In vivo study demonstrated that SeCQDs can significantly ameliorate the Aβ induced memory deficits, reduce Aβ accumulation and inhibit neuron degeneration in AD model rats. The versatility of functionalization and potential ability to cross the blood-brain barrier (BBB) make SeCQDs as prospective nanodrugs for treating AD.